2017
DOI: 10.1097/cad.0000000000000518
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 blockade with AMD3100 enhances Taxol chemotherapy to limit ovarian cancer cell growth

Abstract: The standard of care for ovarian cancer includes initial treatment with chemotherapy. Despite initial efficacy, over 70% of patients develop recurrence; thus, there is a need to identify novel approaches that can improve therapeutic outcomes. We evaluated AMD3100 (Plerixafor), an FDA-approved CXCR4 inhibitor, as a potential adjunctive therapy for low-dose Taxol (Paclitaxel) by assessing the impact on in-vitro ovarian cancer cell proliferation. Proliferation was a measure for both human TOV-112D and murine ID8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…The increase of TAMs following chemotherapy is mostly the result of monocyte recruitment from peripheral circulation, and, to a lesser extent, proliferation of tissue‐resident macrophages . An increased expression of chemotactic agents known to recruit macrophages, including CSF1, CXCL12, and CCL2, are often up‐regulated in tumor cells and tumor‐associated stromal cells in response to cytotoxic chemotherapy . It has also been established that hypoxia induces expression of several chemotactic factors, attracting a variety of BMDCs including monocytes, which differentiate into TAMs expressing the tyrosine kinase receptor TIE2 .…”
Section: Tumor‐associated Macrophages In Response To Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of TAMs following chemotherapy is mostly the result of monocyte recruitment from peripheral circulation, and, to a lesser extent, proliferation of tissue‐resident macrophages . An increased expression of chemotactic agents known to recruit macrophages, including CSF1, CXCL12, and CCL2, are often up‐regulated in tumor cells and tumor‐associated stromal cells in response to cytotoxic chemotherapy . It has also been established that hypoxia induces expression of several chemotactic factors, attracting a variety of BMDCs including monocytes, which differentiate into TAMs expressing the tyrosine kinase receptor TIE2 .…”
Section: Tumor‐associated Macrophages In Response To Chemotherapymentioning
confidence: 99%
“…87,104,109,159,179 An increased expression of chemotactic agents known to recruit macrophages, including CSF1, CXCL12, and CCL2, are often up-regulated in tumor cells and tumor-associated stromal cells in response to cytotoxic chemotherapy. 109,162,180,181 It has also been established that hypoxia induces expression of several chemotactic factors, attracting a variety of BMDCs including monocytes, which differentiate into TAMs expressing the tyrosine kinase receptor TIE2. 179 TIE2 + TAMs are closely associated with tumor vasculature and support angiogenesis in an angiopoietin-2-(ANG2)-dependent manner.…”
Section: Tams In Chemotherapy-induced Metastasismentioning
confidence: 99%
“…66 Importantly, another study detected abundant CXCR7 expression in ovarian cancer tissues and cells. 66 Importantly, another study detected abundant CXCR7 expression in ovarian cancer tissues and cells.…”
Section: Xcl12 S I G Naling In Ovarian C An Cermentioning
confidence: 99%
“…65 They posit that these factors may also act as a chemo-attractants of malignant cells toward the ovaries. 65 Indeed, Reeves et al 66 showed that ovarian cancer cells incubated with a combination treatment of AMD3100 (≤10 μmol/L) and They further showed that blocking the CXCR4 receptor with AMD3100 repressed the migration of tumorigenic cells.…”
Section: Xcl12 S I G Naling In Ovarian C An Cermentioning
confidence: 99%
See 1 more Smart Citation